Interpersonal Communication and Effectiveness of Leadership in Islamic Boarding Schools - Rohidin Rohidin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Kyai's leadership in Islamic boarding schools as the holder of full authority over all policies in managing Islamic boarding schools. The process of organizing education in Islamic boarding schools runs according to and in line with efforts to achieve effective and efficient educational goals. The progress and retreat of Islamic boarding schools cannot be separated from the leadership of the boarding school leaders themselves. The effectiveness of the leadership of Islamic boarding school leaders is one of the factors that determine the success of Islamic boarding schools, which is the desire of every community that is very concerned about the quality and quantity of output from the resulting Islamic boarding school educational institutions. This research is a literature study that examines various sources on interpersonal communication and the effectiveness of ulama leadership in Islamic boarding schools. The results of the literacy studies conducted indicate that the interpersonal communication skills of ulama have an influence on the effectiveness of leadership in Islamic boarding schools.